Relating linguistic reconstructions of plant names in Berber to the archaeobotany of North Africa. (August 2021) - Blench, Roger
Highlights: The paper links the linguistic reconstructions for Berber crop plants and the archaeobotanical evidence for agriculture in North Africa. The paper focuses in particular on the evidence for the Canary Islands, since the dates and modes of settlement are controversial. It proposes that a small number of proto-Berber reconstructions for crops are alos reflected in the Guanche language, in particular figs, barley and wheat. Abstract: The archaeobotany, and in particular the chronology of the introduction and spread of agriculture in North Africa is slowly become better known. Nonetheless, there are many controversies, in particular the extent to which finds of cultivated crops are imports as opposed to indicative of true agriculture. It would therefore be helpful to establish the extent to which the evidence from linguistics reflects the archaeobotany of the region. The principle language of North Africa today is Arabic, interleaved with Berber, especially in Morocco and Algeria. This is obviously a recent phenomenon, and present-day languages are palimpsests, with traces of earlier languages such as Phoenician and Latin marking the introduction of new crops and agricultural techniques. Berber poses a particular problem, as despite its broad geographical range, the languages are all extremely close to one another, suggesting a recent spread, and thus the presence of numerous substrate languages which have now disappeared. The paper reviews the linguistic evidence for the main crops grown in North Africa during the period since the introduction of agriculture and the potential link with the archaeobotany of the region. Terms for the following crops appear to be reconstructible to proto-Berber; Cereals barley, wheat, millet, cereal (general term) Pulses fava bean, lentil, Lathyrus Vegetables onion, carrot Fruits date, grape, olive, fig The paper considers the construction of the North African cultigen repertoire from the viewpoint of borrowings from Punic, Latin, Ancient Egyptian, West African languages and Arabic.